Constructing a Chinese Patent Database of listed firms in China: Descriptions, lessons, and insights. Issue 3 (2nd May 2017) - He, Zi‐Lin; Tong, Tony W.; Zhang, Yuchen; He, Wenlong
Abstract: Although China is now the largest patent filing country in the world, there is little firm‐level research using Chinese patents due to difficulties in integrating Chinese patent data with firm data. To partially address this gap, we construct a Chinese Patent Database linking State Intellectual Property Office (SIPO) patents to all listed firms and their subsidiaries in China, and we are making the database publicly available to the research community. We first develop a computer program to match the assignee names of SIPO patents to the names of listed firms and subsidiaries based on a similarity score, taking into account unique challenges associated with Chinese firm‐names and Chinese characters. High‐scoring likely matches are then checked manually to determine whether they are indeed true matches. The resulting database includes 191, 325 SIPO patents matched to listed firms in China from 1990 to 2010. Using this database, we find a large amount of patenting heterogeneity across firms of different geographic locations, technological foci, and ownership types. We also leverage strengths of the data to conduct a detailed analysis of the patent examination process at the SIPO. Although there is not much difference in the examination process between listed firms and their nonlisted counterparts in China, substantial differences exist between Chinese firms and foreign firms. We find that foreign firms experience substantial delay in publishing patent applications and requesting for substantive examination compared to Chinese firms. Such delay accounts for 40–60% of the longer duration from application date to decision date for foreign firms. However, after accounting for such delay, foreign firms still face much longer pendency in reaching an examination outcome (grant, withdrawal, or refusal) than Chinese firms. We hope that the public database and such analysis will encourage new streams of research on Chinese patents to improve our knowledge of China's fast‐changing innovation landscape.